Evolution and significance of amino acid scores for protein quality - Gaudichon, Claire (Frontiers in Nutrition, 2024)
Amino acid scores have become very popular protein quality scores since their definition and recommendation by FAO expert groups. The chemical score is the central pillar of this method, and has been refined with digestibility correction factors, such as protein digestibility for the PD-CAAS and amino acid digestibility for the DIAAS. Several elements need to be taken into account to properly determine these scores, not only from a methodological point of view but also in order to reconcile regulation, pragmatism, accuracy and also biological significance. This review offers a reminder of the main points raised in the FAO reports on protein and AA requirements in 1995 and 2007, and on protein quality in 1991 and 2013. It also highlights the factors that most impact score metrics, and in particular the choice of reference pattern and protein determination in the food. Lastly, the scores are compared, and versus another quality score based on the physiological response; the protein efficiency ratio.